Continuous monitoring of postirradiation reoxygenation and cycling hypoxia using electron paramagnetic resonance imaging. (27th June 2022) - Kawai, Tatsuya; Matsuo, Masayuki; Takakusagi, Yoichi; Saito, Keita; Hyodo, Fuminori; Devasahayam, Nallathamby; Matsumoto, Shingo; Kishimoto, Shun; Yasui, Hironobu; Yamamoto, Kazutoshi; Krishna, Murali C.
Abstract : Reoxygenation has a significant impact on the tumor response to radiotherapy. With developments in radiotherapy technology, the relevance of the reoxygenation phenomenon in treatment efficacy has been a topic of interest. Evaluating the reoxygenation in the tumor microenvironment throughout the course of radiation therapy is important in developing effective treatment strategies. In the current study, we used electron paramagnetic resonance imaging (EPRI) to directly map and quantify the partial oxygen pressure (pO2 ) in tumor tissues. Human colorectal cancer cell lines, HT29 and HCT116, were used to induce tumor growth in female athymic nude mice. Tumors were irradiated with 3, 10, or 20 Gy using an x‐ray irradiator. Prior to each EPRI scan, magnetic resonance imaging (MRI) was performed to obtain T2‐weighted anatomical images for reference. The differences in the mean pO2 were determined through two‐tailed Student's t ‐test and one‐way analysis of variance. The median pO2 60 min after irradiation was found to be lower in HCT116 than in HT29 (9.1 ± 1.5 vs. 14.0 ± 1.0 mmHg, p  = 0.045). There was a tendency for delayed and incomplete recovery of pO2 in the HT29 tumor when a higher dose of irradiation (10 and 20 Gy) was applied. Moreover, there was a dose‐dependent increase in the hypoxic areas (pO2  < 10 mmHg) 2 and 24 h after irradiation in all groups. In addition, an area that showed pO2 fluctuation between hypoxia and normoxia (pO2  > 10 mmHg) was also identified surrounding the region with stable hypoxia, and it slightly enlarged after recovery from acute hypoxia. In conclusion, we demonstrated the reoxygenation phenomenon in an in vivo xenograft model study using EPRI. These findings may lead to new knowledge regarding the reoxygenation process and possibilities of a new radiation therapy concept, namely, reoxygenation‐based radiation therapy. Abstract : Electron paramagnetic resonance imaging (EPRI) maps the partial oxygen pressure (pO2 ) in tumor tissues. The median pO2 drops after irradiation in a dose‐dependent manner with a tendency for delayed and incomplete recovery (left panel). An area that shows pO2 fluctuation between hypoxia and normoxia—cycling hypoxia—is also depicted surrounding the region with stable hypoxia, and it slightly enlarges after recovery from acute hypoxia (right panel).